If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8v + 6(v + 5) = 18 Reorder the terms: -8v + 6(5 + v) = 18 -8v + (5 * 6 + v * 6) = 18 -8v + (30 + 6v) = 18 Reorder the terms: 30 + -8v + 6v = 18 Combine like terms: -8v + 6v = -2v 30 + -2v = 18 Solving 30 + -2v = 18 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -2v = 18 + -30 Combine like terms: 30 + -30 = 0 0 + -2v = 18 + -30 -2v = 18 + -30 Combine like terms: 18 + -30 = -12 -2v = -12 Divide each side by '-2'. v = 6 Simplifying v = 6
| (1/8)m^3-8n^3=0 | | 8x=8+7x | | 5(x-3)=3(x-4) | | 4*16+8-0/5 | | 300-60+x/2=6x | | 5x^2+6x^2= | | -3x+16=-5 | | y=4x^2-16x | | 10(30)-60+x/2=6x | | 5(p-2)+3(p+1)=25 | | 5-2*(3-6x)=10x | | 4=0.0025p | | -6/7-3/7=4/3u+1/3u | | 5(90-70)=x-126 | | -3(15-3)= | | 2(x+2)-4=30 | | y+(10)=6 | | 1/3y-5/3y=-7/3-1/3 | | -3(x-3)=-36 | | 2w+3=4 | | ln(x-3)=ln(2) | | 3x/2+1=11/2 | | 111-3x=24x+24 | | y=5/2x+6 | | 7x-2x+4-5=3x-1 | | x-60=-17/2(y-20) | | 8p-p+14=1-6p | | 7x+3*(2x-4)=0 | | 2x+3x+7=-43 | | 2(v+8)=9v-47 | | -10=-8v+2(v-8) | | 18+16-5+4= |